Ozone profilE retrieval algorithm (OPERA) for nadir-looking satellite instruments in the UV-VIS - Van Peet, J. C. A. (2014)
For the retrieval of the vertical distribution of ozone in the atmosphere the Ozone ProfilE Retrieval Algorithm (OPERA) has been further developed. The new version (1.26) of OPERA is capable of retrieving ozone profiles from UV-VIS observations of most nadir looking satellite instruments like GOME, SCIAMACHY, OMI and GOME-2. The set-up of OPERA is described and results are presented for GOME and GOME-2 observations. The retrieved ozone profiles are globally compared to ozone sondes for the year 1997 and 2008. Relative differences between GOME/GOME-2 and ozone sondes are within the limits as specified by the user requirements from the Climate Change Initiative (CCI) program of ESA. To demonstrate the performance of the algorithm under extreme circumstances the 2009 Antarctic ozone hole season was investigated in more detail using GOME-2 ozone profiles and lidar data, which showed an unusual persistence of the vortex over the Río Gallegos observing station (51° S, 69.3° W). By applying OPERA to multiple instruments a timeseries of ozone profiles from 1996 to 2013 from a single robust algorithm can be created.